Potential ability of circulating INSL3 level for the prediction of ovarian reserve and IVF success as a novel theca cell–specific biomarker in women with unexplained infertility and diminished ovarian reserve - Pinar Ozcan; F. Sezer; A. Altun; C. Yildiz; H. T. Timur; E. C. Keles; O. Dural; H. S. Taha; E. Saridogan (Reproductive Biology and Endocrinology)
Abstract Background Insulin-like peptide (INSL3), belonging to the insulin-like peptide family, is produced by theca interna cells within antral follicles and the corpora lutea. It is hypothesized that INSL3 is integral to the initial development and function of antral follicles, specifically through its regulatory effect on androgen biosynthesis in the thecal cells of these follicles. Moreover, INSL3 is implicated in the modulation of the ovarian microenvironment, which is essential for facilitating the maturation of oocytes. Our study investigates if circulating and follicular fluid INSL3 levels serve as biomarkers for ovarian reserve and IVF success in women with unexplained infertility (UI) and diminished ovarian reserve (DOR). Methods This prospective study included 75 women (25 with DOR, 24 with UI) undergoing IVF and 26 controls with normal ovarian reserve. Serum and follicular fluid INSL3 levels were measured, and their association with ovarian reserve markers, pregnancy rates, and live birth rates (LBR) was analyzed. Results Circulating (p = 0.001) and follicular fluid (p < 0.001) INSL3 levels, AMH levels (p < 0.001) and AFC (p < 0.001) were significantly lower and basal E2 level (p < 0.001) were significantly higher in DOR group compared to the UI and control groups. Circulating INSL3 positively correlated with serum anti-Müllerian hormone (AMH) and antral follicle count (AFC), and negatively correlated with follicle-stimulating hormone (FSH). Positive pregnancy rates and LBR were significantly lower in the DOR group. Basal FSH was identified as a significant predictor of LBR. Conclusions The current study presents that although the serum and follicular fluid INSL3 levels are significantly lower in women with DOR, the narrow margin between the DOR and control groups indicates that INSL3measurement may be insufficient on its own to be of diagnostic value for DOR. Further research with larger sample sizes is needed to validate these findings and explore the role of INSL3 in ovarian aging and infertility treatment.